Index + Factors + Alpha. Issue 4 (15th October 2021) - Ang, Andrew; Chen, Linxi; Gates, Michael; Henderson, Paul D.
Abstract : We establish, under both theoretical conditions and empirical application, the separate roles of (1) market asset class exposure through index funds; (2) style factor exposure, such as exposure to value, momentum, and quality, which have traditionally delivered higher and differentiated returns than market index exposure; and (3) pure alpha-seeking sources of return in excess of index and factor returns. A new methodology determines optimal allocations of index, factors, and alpha-seeking funds by imposing priors on the information ratios of factors and alpha strategies. We expect in many cases, prior standard deviations for factor funds will be smaller than those for alpha strategies, whereas prior means for alpha strategies may be larger than those for factor funds.